Enhanced Anti-diabetic Effect of Berberine Combined With Timosaponin B2 in Goto-Kakizaki Rats, Associated With Increased Variety and Exposure of Effective Substances Through Intestinal Absorption - Tian, Xiaoting; Liu, Fang; Li, Zhixiong; Lin, Yunfei; Liu, Huan; Hu, Pei; Chen, Mingcang; Sun, Zhaolin; Xu, Zhou; Zhang, Yiting; Han, Li; Zhang, Yuanyuan; et al. (Frontiers in Pharmacology, 2019)
Objective: Inspired by the traditionally clinical application of herb pair Zhimu-Huangbo to treat diabetes, a combination of plant ingredients, timosaponin B2 (TB-2) and berberine (BBR), was evaluated for their anti-diabetic efficacy and cooperative mechanisms. Methods: The efficacy and pharmacokinetics of orally administered TB-2 (33.3 mg/kg/day), BBR (66.7 mg/kg/day) and TB-2+BBR (100 mg/kg/day) were evaluated in spontaneously non-obese diabetic Goto-Kakizaki (GK) rats, and metformin (200 mg/kg/day) was used as a positive control. The comparative exposure of the parent drugs, timosaponin A3 (TB-2 metabolite), and M1-M5 (BBR metabolites) was quantified in the portal vein plasma (before hepatic disposition), liver and systemic plasma (after hepatic disposition) of normal rats on single and combination treatments. Cooperative mechanism of TB-2 and BBR on intestinal absorption and hepatic metabolism were investigated in Caco-2 cells and primary hepatocytes, respectively. Results: After a 6-week experiment, non-fasting and fasting blood glucose levels and oral glucose tolerance test results showed that TB-2+BBR treatments (100 mg/kg/day) displayed significantly anti-diabetic efficacy in GK rats, comparable to that on metformin treatments. However, no significant improvement was observed on TB-2 or BBR treatments alone. Compared to single treatments, combination treatments led to the increased circulating levels of BBR by 107% in GK rats. In normal rats, the hepatic exposure of BBR, timosaponin A3, and M1-M5 was several hundred folds higher than their circulating levels. Co-administration also improved the levels in the plasma and liver by 41%-114% for BBR, 141%-230% for TB-2 and 12%-282% for M1-M5. In vitro, the interaction between TB-2 and BBR was mediated by intestinal absorption, rather than hepatic metabolism. Conclusion: Combining TB-2 and BBR enhanced the anti-diabetic efficacy by increasing the in vivo variety of effective substances, including the parent compounds and active metabolites, and improving the levels of those substances through intestinal absorption. This study is a new attempt to assess the effects of combined plant ingredients on diabetes by scientifically utilizing clinical experience of an herb pair.